Intumescent polypropylene: Interactions between physical and chemical expansion. (24th November 2019) - Bensabath, Tsilla; Sarazin, Johan; Jimenez, Maude; Samyn, Fabienne; Bourbigot, Serge
Summary: To decrease the reaction to fire of a highly flammable plastic, polypropylene (PP), the concept of intumescence was applied. Two intumescent systems were designed on the basis of different mechanisms: physical expansion with expandable graphite (EG) and chemical expansion with modified ammonium polyphosphate (AP). Fire behavior of PP containing EG, AP, or an AP/EG mixture with a total loading of 10 wt% was evaluated by cone calorimetry at 35 kW·m −2 . Thermocouples allowed measuring the temperature at the backside or inside samples over time and evaluating the thermal barrier of these intumescent materials. Two grades of AP (difference in composition) and several grades of EG (difference in expansion characteristics) were compared. Mixing AP and EG does not create a synergistic effect in studied conditions. Contrarily, the incorporation of small amount of EG in PP‐AP modifies heat transfer in the coating, creating a strong anisotropy. Graphite worms are trapped vertically into the expanded AP, which increases the transverse heat conductivity (lower efficiency of the thermal barrier) and decreases the fire performance. This phenomenon disappears in thicker specimens. While a higher expansion volume of graphite worms improves fire performances of PP with only small amount of EG (1 wt%), this effect is not noticeable with AP/EG mixtures.